Varicose veins in very young - Frings, N.; Schubert, R.; Schäfer, L.; Rass, K. (Phlebologie, 2008)
The prevalence of varicose veins in very young patients is rather low. However, since this is not worked out in the literature, we considered on treatment strategies and techniques in this patients. Patients and methods: We included in our study 58 patients younger than 25 years, who presented to our clinic over a one year period. 42 patients revealed primary varicose veins with 68 legs affected. The average age was 21.5 years, 28 were female, 14 male. Due to CEAP 66 legs were classified as C2–C3, and two legs as C4. In 38 legs an incompetence of the saphenofemoral or saphenopopliteal junction (SFJ/ SPJ) was found. Generally, we recommended a conservative treatment approach and to play a waiting game. An active surgical treatment has been indicated in 21 legs based on increasing discomfort despite sufficient conservative therapy, reflux of the greater or lesser saphenous vein down to the ankle (Hach stage IV and III respectively), existence of a secondary deep vein incompetence or a strong patient’s demand. Finally, 15 patients have been treated surgically by flush ligation of the saphenofermoral/popliteal junction (SFJ/SPJ)), ligation of all side branches, oversewing the stump to protect from angiogenesis and complete removal of all superficial varicose veins in tumescent local anaesthesia. Results: After an average follow-up of five months 13 patients were reexamined. All junctional regions were without reflux and recurrent varices were not observed. One minor complication occurred (afferent nerve injury). Conclusion: Although all operations were performed without major complications our strategy is different now. After failure of conservative treatment we would advise at first to an endovenous obliteration. The aim is to gain time in young patients to avoid a first to third recurrence in the age of 40 to 50 years, because even after correctly performed ligation of the SFJ/SPJ recurrences may occur by neovascularization. We would perform an operation only if recurrences after endovenous therapy might develop or when a second endovenous procedure will not be favourable.
Keywords: Varicose vein surgery; treatment strategies; side effects; endovenous laser treatment; radiofrequence obliteration